The Evaluation of Curriculum 2013 Policy on Travelling Business Skill Program At Smkn 4 Mataram - Hairi, Muhtadi; Rosyadi, Unifah; Karnati, Neti; Suhardi, Muhamad (International Journal for Educational and Vocational Studies, 2020)
Vocational High Schools (SMK) are designed to prepare students or graduates who are ready to enter the workforce and are able to develop professional attitudes in their fields. In addition, graduates are required to develop themselves in the path of entrepreneurship, so they can advance in entrepreneurship even in whatever conditions and situations. This policy was adopted after seeing the fact that most of the educated unemployed are secondary education graduates, which can be interpreted as a lack of secondary education graduates' skills to enter the workforce. One of the expertise programs for creating educated graduates at secondary schools is the tourism program. Seeing these conditions, it is necessary to evaluate the implementation of the 2013 curriculum policy on the travel business expertise program. This study uses a program evaluation method with a qualitative approach. The results of this study can be concluded that the evaluation of the program in the context component is in the category of "very good". Likewise, the results of evaluating the implementation of a productive curriculum in the travel business expertise program, the input components include curriculum programs, management of educators and education staff, management of financing and management of the education calendar in the "very good" category. The results of evaluating the curriculum implementation process of productive subjects in business travel expertise in the process components include the planning of the learning process, the implementation of the process, learning, assessment, and supervision of the learning process. The results of the evaluation of the implementation of the curriculum implementation of productive subjects expertise travel business expertise in the process component with the category of "very good". The results of the evaluation of the product component of the travel business expertise program at SMK Negeri 4 Matara with the "very good" category.